Development of Knowledge Management Risk Framework for the Construction Industry - Demirdogen, Gokhan (MDPI, 2023)
The construction industry (CI) has complex, human-based, dynamic, and fragmented structure. Therefore, effective Knowledge Management (KM) is the key to eliminate risks and ensure project success. However, KM applications in CI are behind other industries. Moreover, construction companies try to integrate Information and Communication Technologies and Information Systems. However, their success and adaptation levels are below expectations due to their unawareness of KM risks. Furthermore, there is a lack of knowledge identification, conceptualization, and development of a comprehensive KM risk framework. Therefore, this study aims to identify KM risks and to develop a KM risk framework. The research followed a literature review, Focus Group Discussion (FGD), Fuzzy TOPSIS, and an expert review meeting. Using the Fuzzy TOPSIS methodology, the sequence of KM risks and their weights were uncovered. According to the analysis results, operational KM risks were found more important than technological and human-related factors. In addition, Financial risks were revealed to be the most outstanding risk in KM. As a final step, the expert review meeting was held. The reviews revealed that KM risks are of note and yet ignored. Another inference from expert reviews showed that the developed framework was beneficial to manage KM risks in CI.
Keywords: Knowledge Management; risk management; construction industry; FUZZY TOPSIS; PERFORMANCE; PROJECTS; MODEL; AHP; Construction & Building Technology; Engineering